Meningkatkan Keaktifan Dan Hasil Belajar Siswa Dengan Menggunakan Model PBL Dan Make A Match Pada Pembelajaran Bahasa Indonesia Memahami Isi Teks Eksplanasi Di Kelas 5 SDN Kuin Utara 6 Banjarmasin - Delvi Lestari; Mahmuddin . (CV. ITTC INDONESIA, 2024)
Research problems in the form of low activity, learning activeness and student learning outcomes, this is due to learning that still applies teacher centered, and students have difficulty understanding the contents of explanatory texts in Indonesian language learning. Efforts to overcome these problems by applying PBL and Make a Match learning models which are a combination of models. The purpose of the study was to improve the activities of teachers, students, student learning activeness, and student learning outcomes. This researcher used Classroom Action Research (PTK) which was conducted 4 times a meeting. The subjects of this research were 5th grade students of SDN Kuin Utara 6 Banjarmasin. Qualitative data obtained from observations of teacher activities, student activities, and learning activeness, then quantitative data from learning outcomes obtained through written tests in groups and individuals. The results of this study showed that teacher activity, student activity, and learning activeness increased, the conclusion is that the use of PBL and Make a Match models can optimize teacher activity, student activity. It is recommended to use the model as an alternative to improve learning outcomes.